Menu Close

Question-211979




Question Number 211979 by Spillover last updated on 25/Sep/24
Answered by BHOOPENDRA last updated on 25/Sep/24
∫(dx/((x^2 tan^(−1) x+tan^(−1) x +x^2 π+π)))  ∫(dx/((x^2 +1)(tan^(−1) x+π)))  Let  t=tan^(−1) x+π           dt=(dx/(1+x^2 ))  ∫ (1/t)dt= ln(t)   put t=(tan^(−1) x +π)  ln(tan^(−1) x+π)+c
dx(x2tan1x+tan1x+x2π+π)dx(x2+1)(tan1x+π)Lett=tan1x+πdt=dx1+x21tdt=ln(t)putt=(tan1x+π)ln(tan1x+π)+c
Commented by Spillover last updated on 26/Sep/24
great.thanks
great.thanks

Leave a Reply

Your email address will not be published. Required fields are marked *